Analysis of Scientific Understanding of The Scientific Behavior of Disciplines in Waste Disposal - Vidiyanti; Aliet Noorhayati Sutisno; Fanny Septiany Rahayu (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2025)
Education is a bridge for humans to develop their potential through the learning process obtained. With education, students are able to protect the surrounding environment, especially in the school environment. A clean, comfortable school environment can make learning more enjoyable, increase learning motivation, and support students’ mental and physical health. Science literacy is the ability to understand scientific concepts and processes and utilize science to solve problems in daily life. Based on environmental problems that are increasing day by day, and this is closely related to human behavior. This study aims to describe the scientific understanding of the scientific behavior of discipline in disposing of waste at SDN 1 Plumbon. The type of research used is qualitative research with a descriptive method with instruments using observation, interviews, and documentation as data collection techniques. The results of the study show that students’ scientific understanding of the concept of waste shows that the learning process touches three important domains in education, namely cognitive, affective, and psychomotor. The understanding of science is not just a theory, but also how it is applied in real life, especially in waste management and the formation of scientific behavior. This is shown through students being able to recognize and explain types of waste such as organic, inorganic, and B3 waste. Students are also able to apply understanding through real actions, such as throwing garbage according to its type, sweeping yards, and carrying out pickets. In addition, the scientific behavior of students is reflected in the discipline in maintaining cleanliness, as well as the ability to sort, categorize, and classify waste based on its characteristics and level of danger.